Professional Development and Digital Marketing Strategy Implementation at a Digital Agency - Dzakwan, Muhammad (Journal of Community Services: Sustainability and Empowerment, 2025)
This community service initiative addresses the disparity between theoretical business education and practical industry application within the digital marketing sector. The project focused on Digital Agency with the initials “DC” as the subject of devotion, aiming to foster professional behavioral change and digital literacy. The methods involved immersion in account management, lead generation, and professional event coordination. The service resulted in the transformation of the subject into a prospective business professional capable of managing high-profile client relations and navigating B2B/B2C marketing dynamics. Findings suggest that while individual professional development was successful, organizational efficiency requires decentralized structural changes to sustain community growth.